2001
DOI: 10.13031/2013.6087
|View full text |Cite
|
Sign up to set email alerts
|

Principal Component Regression of Near?infrared Reflectance Spectra for Beef Tenderness Prediction

Abstract: The R 2 was 0.612 when the spectra between 1100 nm and 1350 nm were analyzed. When the second derivatives of the spectral data were used, the R 2 of the PCR model to predict WB shear force of the meat was 0.633 for the full spectral range of 1100 to 2498 nm and 0.616 for the spectral range of 1100 to 1350 nm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(32 citation statements)
references
References 16 publications
1
30
0
1
Order By: Relevance
“…Therefore, the wavelengths from 1400 to 1625 nm were less useful than the wavelengths from 1000 to 1400 nm in discriminating beef tenderness variations. These findings were in agreement with the results reported by Hildrum et al [26] and Park et al [44] on modeling NIR spectra for beef tenderness prediction. Also, the reflectance values of the steaks were less than 3% beyond 1400 nm due to water absorption (Fig.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Therefore, the wavelengths from 1400 to 1625 nm were less useful than the wavelengths from 1000 to 1400 nm in discriminating beef tenderness variations. These findings were in agreement with the results reported by Hildrum et al [26] and Park et al [44] on modeling NIR spectra for beef tenderness prediction. Also, the reflectance values of the steaks were less than 3% beyond 1400 nm due to water absorption (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…VIA systems were used to relate image textural features to beef muscle structure [24,43], while near-infrared spectroscopic systems were used to relate spectral reflectance measurements to chemical composition of beef [26,44]. In this study, hyperspectral imaging was implemented for beef tenderness prediction.…”
Section: Introductionmentioning
confidence: 99%
“…The best results were achieved in predicting the tenderness of beef. Park et al applied PCR on NIR reflectance spectra of beef to predict its tenderness [172]. It was found that tough meat has an overall higher absorption than tender meat at all wavelengths.…”
Section: Grain Quality Inspectionmentioning
confidence: 99%
“…Mitsumoto et al (1991) pioneered the use of spectroscopy for beef tenderness prediction and obtained an accuracy of 68% in predicting tenderness. Subsequently several additional studies reported moderate to promising results in predicting beef tenderness (Hildrum et al, 1994(Hildrum et al, , 1995Rødbotten et al, 2001;Park et al, 1998;Jeyamkondan and Kranzler, 2003;Liu et al, 2003). However, contradictory results have been reported in the literature regarding the use of spectroscopy for beef tenderness prediction.…”
Section: Introductionmentioning
confidence: 99%
“…VIA systems were used to relate image textural features to beef muscle structure (Zheng et al, 2006;Du and Sun, 2006), while spectroscopic systems were used to relate spectral reflectance measurements to chemical composition of beef (Park et al, 2001;Hildrum et al, 1994). VIA and spectroscopy are two promising nondestructive methods, but have achieved only limited success for predicting beef tenderness.…”
Section: Introductionmentioning
confidence: 99%